Calendar Aging and Gas Generation in Commercial Graphite/NMC-LMO Lithium-Ion Pouch Cell. Issue 14 (11th November 2017) - Mao, Z.; Farkhondeh, M.; Pritzker, M.; Fowler, M.; Chen, Z.
Abstract : The calendar life of a commercial graphite/NMC-LMO lithium-ion battery is assessed under various storage temperature (35°C and 60°C) and state-of-charge (0% and 100%) conditions. Virtually no degradation is observed for cells stored at 0% SOC as expected, whereas those aged for 9 months in a fully charged state at 35°C and 60°C lose ∼10% and ∼43% of their capacity, respectively. Differential-voltage analysis of periodic cell cycling data and post-mortem examination of the aged electrodes are used to identify degradation modes. Three main sources of high-temperature capacity loss are identified: i) electrode dry-out due to gas formation (∼30%), ii) loss of cyclable lithium (∼10%) and iii) cathode active material loss (∼3%). Cells stored at a lower temperature of 35°C experience little gas generation and degrade primarily through the loss of Li inventory. The analysis shows that similar amounts of cyclable Li are consumed by side reactions during calendar aging at both storage temperatures of 35°C and 60°C. Non-destructive compression (1.0–5.0 psi) of the aged pouch cells during discharge is shown to improve their capacity by ∼15%. This effect is attributed to the redistribution of gas bubbles inside the pouch cell by the applied pressure.